2014
DOI: 10.5897/ajb2013.13479
|View full text |Cite
|
Sign up to set email alerts
|

High xylanase production by Trichoderma viride using pineapple peel as substrate and its apllication in pulp biobleaching

Abstract: Xylanases are hydrolases which depolymerize the xylan components present in plants cell wall. Commercial applications for these enzymes include its use in the pulp bleaching, food and animal feed industries, among others. Recently, there is a great interest on the exploitation of agro-industrial wastes as low-cost raw materials for value-added compounds production, as xylanolytic enzymes for industrial applications. This is the first report about the xylanase production using pineapple peel as substrate. The x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 38 publications
(53 reference statements)
1
5
0
Order By: Relevance
“…For instance, the cellulase-free xylanase from Trichoderma viride was used on kraft pulp from Eucalyptus grandis, resulting in a decrease in its Kappa number and its maintenance of viscosity compared to those of the control, with parameters (enzyme dose, time, temperature, and pH). The results indicated that the enzyme showed potential for use in the pulp and paper industry (Fortkamp and Knob, 2014). Similar studies by Guimarães et al (2013) using a xylanase from Aspergillus aculeatus var aculeatus in the pretreatment of E. grandis pulp, and by Silva et al (2016) described the effective use of xylanase from Penicillium crustosum to bleach the kraft pulp of E. grandis, obtained a significant reduction in Kappa number (5.27 points) corresponding to a 35.04% Kappa efficiency.…”
Section: Application Of Thermostable Xylanases In Industrial Processessupporting
confidence: 58%
“…For instance, the cellulase-free xylanase from Trichoderma viride was used on kraft pulp from Eucalyptus grandis, resulting in a decrease in its Kappa number and its maintenance of viscosity compared to those of the control, with parameters (enzyme dose, time, temperature, and pH). The results indicated that the enzyme showed potential for use in the pulp and paper industry (Fortkamp and Knob, 2014). Similar studies by Guimarães et al (2013) using a xylanase from Aspergillus aculeatus var aculeatus in the pretreatment of E. grandis pulp, and by Silva et al (2016) described the effective use of xylanase from Penicillium crustosum to bleach the kraft pulp of E. grandis, obtained a significant reduction in Kappa number (5.27 points) corresponding to a 35.04% Kappa efficiency.…”
Section: Application Of Thermostable Xylanases In Industrial Processessupporting
confidence: 58%
“…Interestingly, Zn 2+ increases its α -helix content from 45.3 to 46.8%. Moreover, Zn 2+ has also been reported to be the activator of several enzymes, including carbonyl reductase [47], xylanase [48], nattokinase [49] and lipase [50]. The tendency for a difference between Zn 2+ and other metal ions may be due to the different structural compatibility of metal ions to bind with YlER.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Xylan is a major structural component of plant cell walls and its degradation requires the action of several enzymes, among which endoxylanases (EC 3.2.1.8) play a key role (Polizeli et al, 2005;Fortkamp and Knob, 2014). Xylanases occur widely in bacteria, yeasts and fungi.…”
Section: Introductionmentioning
confidence: 99%